Oral erythromycin for treatment of gastrointestinal dysmotility in premature infants - Armelia Moesri; Bugis Mardina Lubis; Asrul Asrul; Atan Baas Sinuhaji; Guslihan Dasa Tjipta (Paediatrica Indonesiana, 2007)
Background Functional immaturity of gastrointestinal (GI)motility predisposes preterm infants to feeding intolerance.Erythromycin as a prokinetic agent has been given to preterminfants for the management of non-obstructive GI dysmotility.Objective To evaluate the efficacy of oral erythromycin for thetreatment of GI dysmotility in preterm infants.Methods A randomized controlled clinical trial was done at AdamMalik Hospital and Pirngadi Hospital, Medan, between October2004 – March 2005. Fifty preterm infants with feeding intolerancewere randomly assigned to either receive oral erythromycin (12.5mg/kg, every 6 hours) or placebo for 7 days. Improved tolerancefor enteral feedings was evaluated by the amount of gastric residuebefore feeding.Results On the sixth day, there was a significant difference in theamount of residue from gastric residue between the oralerythromycin group and placebo group (mean 21.7 and 29.4;P<0.05) and so were results on the seventh day (mean 14.1 and26.9; P<0.05).Conclusion Oral erythromycin reduces the amount of gastricresidue before feed in premature infants.